Disruption of exogenous eGFP gene using RNA-guided endonuclease in bovine transgenic somatic cells. Issue 6 (26th November 2014) - Choi, WooJae; Yum, SooYoung; Lee, SongJeon; Lee, WonWu; Lee, JiHyun; Kim, SeokJoong; Koo, OkJae; Lee, ByeongChun; Jang, Goo
Summary: Genome-editing technologies are considered to be an important tool for generating gene knockout cattle models. Here, we report highly efficient disruption of a chromosomally integrated eGFP gene in bovine somatic cells using RNA-guided endonucleases, a new class of programmable nucleases developed from a bacterial Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 system. In the present study, we obtained homogenously eGFP-expressing primary fibroblasts from cloned bovine transgenic embryonic tissues and employed them for further analysis. CRISPR/Cas9 plasmids specifically targeting the eGFP gene were transfected into the eGFP fibroblasts by electroporation. After 10 days of culture, more than 40% of the cells had lost eGFP expression in fluorescence activated cell sorting (FACS) analysis. Targeted sequences of the transfected cells were analyzed, and various small indel mutations (6–203 bp deletions) in the target sequence were found. The fibroblasts mutated with the CRISPR/Cas9 system were applied for somatic cell nuclear transfer, and the reconstructed embryos were successfully developed into the blastocyst stage. In conclusion, the CRISPR/Cas9 system was successfully utilized in bovine cells and cloned embryos. This will be a useful technique to develop livestock transgenesis for agricultural science.